On Truth and Opacity. Symbolic Translation and Legibility in Contemporary Text-Based Cuban Art - Garrido Castellano, Carlos (2018)
this paper examines text-based artworks that employ symbolic translations as a way of analyzing the discursive constrains regulating the Cuban public sphere. Through a revision of artistic projects that turn to translation and intend to provoke the spectator’s active engagement, I seek to understand which possibilities are opened by translation in order to escape the burdens of representation and commoditization shaping contemporary Cuban art. I argue that the encouragement of direct experience could be framed as that possible alternative. The potential attributed to experience and practicality, nevertheless, cannot be directly deduced from the artist’s intentions, being contingent ultimately of how each project works.